2021
DOI: 10.1136/bmjopen-2020-045655
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of acupuncture in refractory irritable bowel syndrome: study protocol for a randomised controlled trial

Abstract: IntroductionIrritable bowel syndrome (IBS) is a common chronic functional gastrointestinal disorder that presents with abdominal pain/discomfort and altered bowel patterns. IBS has multiple potential causes for which conventional medicines have had limited success, resulting in a significant number of patients who do not sensitively respond to pharmacotherapy for a period of 12 months and who develop a continuing symptom profile (described as refractory IBS) and seek help through (non)pharmacological treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…There are four domains: absenteeism (percentage of work hours missed because of IBS); presenteeism (percentage of impairment experienced at work because of IBS); overall work impairment (percentage of work productivity loss); or activity impairment (percentage impairment in activities of daily living). We also used the work and social adjustment scale (WSAS), 37 which has been used by others to measure impact of IBS on ability to work, manage at home, engage in social or private leisure activities, or maintain close relationships 38–41 . The five domains are scored on a 9‐point scale from “not at all” (score 0), through “definitely” (score 4), to “very severely” (score 8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are four domains: absenteeism (percentage of work hours missed because of IBS); presenteeism (percentage of impairment experienced at work because of IBS); overall work impairment (percentage of work productivity loss); or activity impairment (percentage impairment in activities of daily living). We also used the work and social adjustment scale (WSAS), 37 which has been used by others to measure impact of IBS on ability to work, manage at home, engage in social or private leisure activities, or maintain close relationships 38–41 . The five domains are scored on a 9‐point scale from “not at all” (score 0), through “definitely” (score 4), to “very severely” (score 8).…”
Section: Methodsmentioning
confidence: 99%
“…We also used the work and social adjustment scale (WSAS), 37 which has been used by others to measure impact of IBS on ability to work, manage at home, engage in social or private leisure activities, or maintain close relationships. [38][39][40][41] The five domains are scored on a 9-point scale from "not at all" (score 0), through "definitely" (score 4), to "very severely" (score 8). We dichotomised presence (score ≥4 ("definitely" impacting)) or absence (score <4) of an impact of IBS on home management activities, social or private leisure activities, or maintaining close relationships.…”
Section: Impact Of Ibs On Work and Activities Of Daily Livingmentioning
confidence: 99%
“…A study showed that acupuncture at Neiguan (PC 6) regulates the vagus nerve (26). A multicenter, large-sample, doubleblind randomized controlled study found that acupuncture at bilateral Tianshu (ST 25), Shangjuxu (ST 37), Neiguan (PC 6), and Zusanli (ST 36) was effective at relieving symptoms in chronic functional gastrointestinal disorder (27). Based on these previous studies, we chose the Hegu (LI 4) and Neiguan (PC 6) points to explore the efficacy of acupuncture in inhibiting colonic spasm during endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…in the IBS population where high placebo responses are common (49). The ongoing randomized sham-controlled trials [NCT04276961 (50), ChiCTR2100044762] will clarify the efficacy of acupuncture compared with sham-acupuncture. And more shams, which are unlikely to have physiological effects, would be necessary for further research.…”
Section: Principal Findings and Comparison With Other Studiesmentioning
confidence: 99%